Skill shift automation and the future of the workforce - Bughin, Jacques [Verfasser]; Hazan, Eric [Verfasser]; Lund, Susan [Verfasser]; Dahlström, Peter [Verfasser]; Wiesinger, Anna [Verfasser]; Subramaniam, Amresh [Verfasser] (My University, 2018)
"Automation and artificial intelligence (AI) are changing the nature of work. In this discussion paper, part of our ongoing research on the impact of technology on the economy, business,and society, we present new findings on the coming shifts in demand for workforce skills and how work is organized within companies, as people increasingly interact with machines in the workplace. We quantify time spent on 25 core workplace skills today and in the future for the United States and five European countries, with a particular focus on five sectors: banking and insurance, energy and mining, healthcare, manufacturing, and retail." (Text extract, BIBB-Doku)
Keywords: G 2.3 Wandel von Arbeit & Wirtschaft; G 2.3.4 Qualifikationswandel; Zukunft der Arbeit; Kompetenzentwicklung; Industrie 4.0; Automatisierung; Künstliche Intelligenz; Internationaler Vergleich; Qualifikationswandel; Prognose